Pure and Applied Chemistry : The Scientific Journal of IUPAC (De Gruyter, 1960)
Pure and Applied Chemistry is the official monthly Journal of the International Union of Pure and Applied Chemistry (IUPAC), with responsibility for publishing works arising from those international scientific events and projects that are sponsored and undertaken by the Union.